As vogais médias pretônicas no falar de Uberlândia: um estudo variacionista - Costa, Priscila Marques (2017)
This research aims to investigate the variable lowering of pre-stressed mid vowels in Uberlândia-MG. To develop this study, we based mainly on the theoretical-methodological assumptions of Labov (2008). The corpus of this research was composed of 24 interviews that are part of GEFONO's database (Group of Studies in Phonology, at Federal University of Uberlândia). The participants were stratified according to three extra-linguistic variables: gender (male and female); age (form 15 to 25, from 26 to 49 and older than 49) and educational level (between 0 and 11 years of study and above 11 years of study). In addition, the participants should be natural of Uberlândia and never have lived out of this city. The linguistic variables considered were: mode of articulation of the preceding context to the pre-stressed vowel; point of articulation of the preceding context; mode of articulation of the following context to the pre-stressed vowel; point of articulation of the following context; stressed vowel height; stressed vowel quality; distance from stressed vowel to vowel of pre-stressed syllable; distance from the pre-stressed vowel in relation to the beginning of the word and type of pre- stressed syllable. The data were encoded and submitted to the statistical analysis program GoldVarb X, whose rounds resulted in a total of 2,549 occurrences, of which 1,608 refer to the vowel /e/ and 941 to the vowel /o/. In 298 occurrences, there was the realization of [e], while the realization of [□] had 176 occurrences. The variable vowel height of the stressed vowel was the main favored of the variant mid-low in the dialect of Uberlândia, which characterizes the lowering through vowel harmony, since the presence of a mid-low vowel in the stressed syllable was selected by the program as the greatest favoring of lowering in both vowels analyzed. Therefore, the results showed that, in Uberlândia's speech, the realization of mid-high vowels pre-stressed prevails, but with the considerable presence of the variant mid- low, especially when there is a mid-low vowel in the stresed syllable, which demonstrates the variability of the investigated phenomenon.